Pengaruh Internet, Kesejahteraan, Entrepreneur, Pangsa Pasar, dan Nilai Ekspor terhadap Economic Complexity (Studi Kasus: 9 Negara Anggota ASEAN 2009-2018) - Ryan Bramastama; Hadi Sasana (Universitas Diponegoro, 2021)
In recent years, almost all ASEAN members have experienced an increase in the value of the economic complexity index. This change can be seen in the improved ranking of ASEAN members in the economic complexity index. Growth can be driven by the process of diversification in knowledge to produce goods that are more sophisticated and more complex. The key to growth in economic complexity is relocated activities from less complex sectors to more complex sectors. More complex sectors require more knowledge to produce goods. The purpose of this study is to examine the effect of the internet, prosperity, entrepreneur, market share and total export on economic complexity in 2009-2018 in ASEAN member countries. This study uses secondary data with a panel data of 90 observations. The analytical tool used in this research model is Generalized Least Square. The results in this Study indicate that the internet, entrepreneur, and total export have positive and significant effect on economic complexity. Prosperity and Market share have negative and significant effect on economic complexity.